თავაზიანი მიმართვის სოციოლინგვისტური წესები მეგრულსა და ლაზურში - გერსამია რუსუდან (ენათმეცნიერების საკითხები, 2025)
The sociolinguistic rules of polite address, based on the principles of alternation and co-occurrence, were developed by the American linguist Susan Ervin-Tripp. The present paper attempts to verify these rules in two unwritten languages of the Kartvelian group, Megrelian and Laz. In the languages under analysis, the inventory of address forms includes nominal, pronominal and verbal elements. In establishing the rules of address, particular importance is given to their interaction with grammatical number, especially the use of plural forms. In Megrelian, polite and familiar terms show the following alternation patterns: Nominal terms: p’at’oni+FN / FN Pronominal terms: tkva (V) / si (T) Verb terms: zoǯ- (polite root)+-t (PL) / rt- (go, stand up, be)+-t (PL); tk- (say)+-t (PL); xod- (sit)+-t (PL) In contrast, Laz displays only one type of alternation (1): Nominal terms: +FN-effendi / FN; Unlike Megrelian, Laz lacks both a T-V opposition and semantically polite verb roots. The following co-occurrence rules can be stated for Megrelian: If a speech act contains a predicate based on the root zoǯ (used as a polite verbal term of address), it co-occurs with either a T or V pronoun and a polite nominal term of address; If a speech act contains the nominal term +FN, it co-occurs with either a zoǯ-based verb or another verb marked with +-t (honorific marker); in this case, the co-occurring pronoun used is tkva (V); If a speech act contains any other predicate marked with the suffix -t and refers to a single addressee, it co-occurs with tkva, indicating that the suffix is an honorific marker. Conversely, if tkva is used for a single addressee, it necessarily co-occurs with either a zoǯ-based verb or another verb marked with +-t (honorific marker). As for Laz, since the T–V opposition is not expressed and there is no zoǯ-root in the language, a single rule can be established based on the principle of co-occurrence, taking into account forms of address: +FN efendi (polite only); –FN (either polite or familiar).